Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s13201-014-0189-3
|View full text |Cite
|
Sign up to set email alerts
|

Reclamation of highly calcareous saline-sodic soil using low quality water and phosphogypsum

Abstract: The efficiency of two amendments in reclaiming saline sodic soil using moderately saline (EC) and moderate sodium adsorption ratio (SAR) canal water was investigated. Phosphogypsum (PG) and reagent grade calcium chloride were applied to packed sandy loam soil columns and leached with canal water (SAR = 4, and EC = 2.16 dS m-1). Phosphogypsum was mixed with top soil prior to leaching at application rates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 22 publications
(19 reference statements)
2
8
0
3
Order By: Relevance
“…In the current study,during the second year after soil amendment applications, ESP values were reduced by almost 50% on gypsum and sulfur treatments compared to those on control sites (Table 3). Gharaibeh et al (2014) conducted an experiment in southern Jordan on a sandy loam Typic Xerachrept soil for reclamation of saline-sodic soil using phosphogypsum and calcium chloride at application rates between 5-40 Mg ha -1 . They stated that ESP values of soil were reduced by 90% for all rates of these amendments.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study,during the second year after soil amendment applications, ESP values were reduced by almost 50% on gypsum and sulfur treatments compared to those on control sites (Table 3). Gharaibeh et al (2014) conducted an experiment in southern Jordan on a sandy loam Typic Xerachrept soil for reclamation of saline-sodic soil using phosphogypsum and calcium chloride at application rates between 5-40 Mg ha -1 . They stated that ESP values of soil were reduced by 90% for all rates of these amendments.…”
Section: Discussionmentioning
confidence: 99%
“…Open Access [4,5]. 지 난 수십년 간의 해외 선행연구를 통해 토양 양분 및 작물 생 산량 증가 [6][7][8], 토양 물리성 개선 [5], 염분 정화 [9,10], 그리 고 산성토양의 알루미늄 독성완화 [11,12]…”
Section: Research Articleunclassified
“…Al-Muhamdi (10) obtained the low values of sodium adsorption ratio and increases the values of the electrical conductivity and the concentration of dissolved calcium in the soil by adding phosphogypsum. It was also found that the addition of phosphogypsum to saline -sodic soil resulted in a significant decrease in the values of sodium adsorption ratio, percentage of sodium exchange and increased of calcium in soil (17). Humic acids (humic acid and folvic acid) are organic amendments of saline soils.…”
Section: Introductionmentioning
confidence: 99%